Covid-19 as a critical incident: Reflection on language assessment literacy and the need for radical changes. (December 2021) - Tian, Wenwen; Louw, Stephen; Khan, Muhammad Kamal
Abstract: Three participant-researchers explored their language assessment literacy (LAL) in the context of school shutdowns during the Covid-19 pandemic in three Asian countries: China, Thailand, and Pakistan. We employed a duoethnographic approach to explore our understandings of LAL, our experiences in language assessment practices, and our perspectives on our professional development during the disruption. Data were collected in January and February 2021, a point at which the school shutdowns had become a reality for teachers across Asia. Data included written narrative reflections and Zoom discussions framed as reflection-on-action, reflection-in-action, and reflection-for-action, focusing specifically on assessment issues. Our initial reflections show a lack of confidence in our LAL and a perception of assessment as highly theoretical. As the study progressed, our reflections on assessment become more confident with increasingly sensitive topics, including the value of training and our role as assessment practitioners in the hierarchical bureaucracy. This study highlights that remote reflections with colleagues across cultures and contexts may be highly constructive in promoting professional development. It is recommended that front-line teachers be given opportunities to develop their own LAL through interfacing with other professionals through reflective practice within and beyond their cultural contexts.